STRONTIUM, δ18O AND δ13C AS PALAEO-INDICATORS OF UNCONFORMITIES: CASE OF THE ALEG AND ABIOD FORMATIONS (UPPER CRETACEOUS) IN THE MISKAR FIELD, SOUTHEASTERN TUNISIA - Mabrouk A.; Belayouni H.; Jarvis I.; Moody R.T.J. (My University, 2006)
A carbon and oxygen stable-isotope study was undertaken on samples from the uppermost Turonian-Santonian Aleg Formation and the Campanian-lowest Maastrichtian Abiod Formation from four wells in the Miskar Field (W1, W2, W3, and W4), Gulf Gabès, offshore southeastern Tunisia. The strontium contents of the same samples were also determined. Carbon isotopes generally yielded values typical of Upper Cretaceous chalks. Calculation of palaeotemperatures using the δ18O data obtained from the analysis of whole-rock samples from the four wells, in most cases generated higher values than those believed to characterize Santonian-Campanian ocean surface waters. This general negative shift in δ18O values is thought to be related to alteration that has resulted from burial diagenesis. Strontium contents in the Abiod Formation are typical of Cretaceous - Tertiary chalks. Top Aleg samples are depleted by around -0.6‰ δ18O and -0.1‰ δ13C compared to the Abiod samples, and by up to -300 μg/g Sr. Depletion in δ 13C, δ18O and strontium in the Aleg Formation is attributed to alteration by meteoric waters, indicating that the top of the Formation has been subject to both meteoric and burial diagenesis. This contrasts with the Abiod Formation which yields unaltered δ13C and strontium values, and oxygen-isotope data which, although lighter than those typical of pristine Upper Cretaceous sediments, are heavier than those recorded in the Aleg Formation, suggesting that only burial diagenesis has affected the younger sediments. In our case, the use of the oxygen data for the calculation of marine palaeotemperatures is not reliable. The strontium concentration, oxygen and carbon stable-isotope data indicate the presence of an unconformity between the Abiod Formation and the Aleg Formation, with possible subaerial exposure of the top of the Aleg Formation, probably during the Coniacian-Santonian and earliest Campanian. This result is consistent with the biostratigraphy of the four wells which confirms that an unconformity exists between the two formations. Copyright © 2006 by The Geochemical Society of Japan.
Keywords: CARBON AND OXYGEN STABLE-ISOTOPES; CHALK; CRETACEOUS; STRONTIUM; TUNISIA; Mesozoic::Cretaceous; Мезозой::Меловая